AUTOMATION OF THE GENERATION OF ELECTRONIC PRODUCT PASSPORTS IN MANUFACTURING PROCESSES - Tileubek Nuraman; Malikov Almas (Theoretical Hypotheses and Empirical Results, 2026)
This paper presents the development of a software module for automated electronic product passport (EPP) generation in machine-building enterprises. The regulatory framework of the Republic of Kazakhstan in the field of electronic product documentation was analyzed. An Event-Driven Architecture based on .NET 8 microservices with integration into MES, ERP, PDM, and SCADA systems was proposed. Hyperledger Fabric blockchain technology with SHA-256 hash storage was applied to ensure record immutability. System validation was conducted at Astana-Mashzavod LLP (September 2024 – February 2025): 342 electronic passports were generated. Passport generation time was reduced 18-fold, error rate decreased by 90.6%, and data completeness increased to 98.4%. The total annual economic effect amounted to 8.8 million KZT with a payback period of 9.3 months